Pengaruh Pelaksanaan Supervisi terhadap Kinerja dan Profesional Guru Sekolah Dasar - Arrum Meirisa; Hadiyanto Hadiyanto (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
Education is one of the most important things in human life. It can be categorised into formal and informal education. The former one is carried out in an institution called school. Lately, the issues regarding the low quality of education in Indonesia has been discussed. To date, Public demands on the quality of education have always been highly anticipated by various parties. The quality of education in formal education certainly involves the teacher, as the main foundation for creating high-quality generations. The role of the teacher is inseparable from the teaching profession in improving Human Resources (HR). Currently improving teacher quality can be seen from the performance and professionalism of a teacher which can be done with supervision. Supervision is an activity that is certainly designed to improve the quality of teachers in certain institutions. However, at this time supervision is said to not have a major effect on improving teacher performance and professionalism in carrying out their duties. This can be seen by the teacher only teach well when there is supervision at the time. The effect of improving the quality of education is not experiencing a good quality improvement. The low performance and professionalism of teachers based on teacher competency makes teachers incompetent. This should be done by the teacher without any connection at the time of supervision. Therefore, there is a need for supervision that has an impact on teachers’ performance and professionalism.